The Design Thinking Process of Creating Emojis as Visually Cultural Embodiments for the Naxi Community, China and their Functions of Stimulating In-Group Well-Being Index in the Digital Age - Yun, Ji; Bin Bianus, Addley Bromeo (Dirasat: Human and Social Sciences, 2025)
Objectives: An effort to create culturally situated emojis for the Naxi community is the focus of this essay, which delves into the user-centered research process that ran through the project. With the guidance of local authorities, this endeavor sought to tackle the discontent of Naxi aboriginals regarding existing emojis, with the goals of enhancing online communication efficiency within the community, digitally preserving and disseminating indigenous culture, and attracting tourists for economic benefit. Methods: A one-month user-centered design process involved local stakeholders to create design alternatives that resonated with the prevailing live, ethnically cultural context identified during fieldwork. Employing design-thinking methodology, participants acted as guides, storytellers, performers, and feedback providers, leading to the development of culturally relevant emojis. Results: This design approach not only met the explicit online communication needs of the local government and indigenous people but also contributed to the implicit goal of enhancing well-being index within the Naxi community. Conclusions: This project showcases an effective strategy for promoting positive well-being and cultural preservation through digital innovation. Importantly, to better suit the unique context of this study and future similar design endeavors, a new design-thinking theoretical model is proposed, emphasizing the dynamic adaptation between user centrality and objectivity centrality to further ensure the reliability and validity of analytical thinking in the design-thinking process.